Trans-complementation of the second step of pre-mRNA splicing by exogenous 5' exons. - Chanfreau, G (1999)
During splicing of nuclear pre-mRNAs, the first step liberates the 5' exon (exon 1) and yields a lariat intron-3'exon (intron-exon 2) intermediate. The second step results in exon ligation. Previous results indicated that severe truncations of the 5' exon of the actin pre-mRNA result in a block to the second splicing step in vitro in yeast extracts, leading to an accumulation of intron-exon 2 lariat intermediates. We show that exogenous exon 1 RNA oligonucleotides can chase these stalled intermediates into lariat intron and spliced exons. This reaction requires some of the cis elements and trans-acting factors that are required for a normal second step. There is no strong sequence requirement for the exon 1 added in trans, but oligonucleotides with complementarity to the U5 snRNA conserved loop perform the chase more efficiently. Using a dominant negative mutant of the DEAH-box ATPase Prp16p and ATP depletion, we show that the stalled intermediate is blocked after the Prp16p-dependent step. These results show that exogenous RNAs with various sequences but containing no splicing signals can be incorporated into spliceosomes and undergo RNA recombination and exon shuffling during the second step of pre-mRNA splicing.